2021
DOI: 10.3389/fimmu.2021.754208
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor Enhances the Alternatively Activated Macrophages and Promotes Biliary Injuries Caused by Helminth Infection

Abstract: The autonomic nervous system has been studied for its involvement in the control of macrophages; however, the mechanisms underlying the interaction between the adrenergic receptors and alternatively activated macrophages (M2) remain obscure. Using FVB wild-type and beta 2 adrenergic receptors knockout, we found that β2-AR deficiency alleviates hepatobiliary damage in mice infected with C. sinensis. Moreover, β2-AR-deficient mice decrease the activation and infiltration of M2 macrophages and decrease the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…These authors also showed that infection of mice resulted in mixed M1 and alternatively activated macrophages (M2) ( Kim et al, 2017a ). The percentage of M1 and M2 macrophages were different according to the stage of the infection with the increase in M1 macrophages in the early stage of infection, while the M2 macrophages were predominant in the late stage of the infection especially in the fibrotic part ( Kim et al, 2017a ; Koda et al, 2021 ). Besides, the various components of C. sinensis induces the differentiation of macrophages to both M1 and M2 macrophages ( Wi et al, 2012 ; Kim et al, 2017a ; Yan et al, 2020a ; Kang et al, 2020 ; Koda et al, 2021 ).…”
Section: Mechanism Of Immunity To Clonorchis Sinensismentioning
confidence: 96%
See 4 more Smart Citations
“…These authors also showed that infection of mice resulted in mixed M1 and alternatively activated macrophages (M2) ( Kim et al, 2017a ). The percentage of M1 and M2 macrophages were different according to the stage of the infection with the increase in M1 macrophages in the early stage of infection, while the M2 macrophages were predominant in the late stage of the infection especially in the fibrotic part ( Kim et al, 2017a ; Koda et al, 2021 ). Besides, the various components of C. sinensis induces the differentiation of macrophages to both M1 and M2 macrophages ( Wi et al, 2012 ; Kim et al, 2017a ; Yan et al, 2020a ; Kang et al, 2020 ; Koda et al, 2021 ).…”
Section: Mechanism Of Immunity To Clonorchis Sinensismentioning
confidence: 96%
“…The percentage of M1 and M2 macrophages were different according to the stage of the infection with the increase in M1 macrophages in the early stage of infection, while the M2 macrophages were predominant in the late stage of the infection especially in the fibrotic part ( Kim et al, 2017a ; Koda et al, 2021 ). Besides, the various components of C. sinensis induces the differentiation of macrophages to both M1 and M2 macrophages ( Wi et al, 2012 ; Kim et al, 2017a ; Yan et al, 2020a ; Kang et al, 2020 ; Koda et al, 2021 ). Moreover, it has been shown that macrophages are associated with the resistance of mice to the second infection by C. sinesis , which showed the decrease of IL-10 and IL-13 produced by M2 macrophages and increases of specific IgE, IgG1, and IgG2a levels in serum at 1 week or 4 weeks following re-infection ( Kim et al, 2017b ).…”
Section: Mechanism Of Immunity To Clonorchis Sinensismentioning
confidence: 96%
See 3 more Smart Citations